PATIENT ADMINISTRATION SYSTEM IN OUTPATIENT CLINIC ARTHA SARI USING VISUAL BASIC 6.0 - Suprih Andayani; IRE Puspa Wardani, Ir., MMSI IRE Puspa Wardani, Ir., MMSI (Jurnal Sistem Informasi, 2004)
Artha Sari on during this clinic revenue administration system outpatients is still donemanually so that often lead to errors and delays in outpatient information.Based on the above issues I am interested to try to help resolve the problem by createa system of computerized and the author will use the display program Visual Basic6.0.